2016
DOI: 10.1021/acssuschemeng.5b01752
|View full text |Cite
|
Sign up to set email alerts
|

Properties of Cellulosic Material after Cationization in Different Solvents

Abstract: Fibers resulting from pulping of wood are negatively charged by nature. Both the cellulose and hemicelluloses contribute to the anionicity. The negative charge of cellulosic material can be reversed with the same reagent commonly used for the cationization of starch. In this study, a bleached Kraft pulp was cationized in systems with different water-miscible organic solvents. Replacing 90% of the water with isopropanol and particularly with tetrahydrofuran yielded higher degrees of substitution and increased r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
30
0
1

Year Published

2017
2017
2021
2021

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 61 publications
(33 citation statements)
references
References 34 publications
2
30
0
1
Order By: Relevance
“…34 Other solvents have also been studied to minimize the epoxide ring opening reaction with water, which consumes the reagent and decreases the reaction efficiency. 35,36 Depending on the reaction conditions (e.g. solvent content, time, and temperature), CNFs with charge densities of 0.…”
Section: Cationization Of Woodmentioning
confidence: 99%
“…34 Other solvents have also been studied to minimize the epoxide ring opening reaction with water, which consumes the reagent and decreases the reaction efficiency. 35,36 Depending on the reaction conditions (e.g. solvent content, time, and temperature), CNFs with charge densities of 0.…”
Section: Cationization Of Woodmentioning
confidence: 99%
“…2900 cm 1 , which is due to asymmetric and symmetric CH stretching (Collier et al 1997;Schwanninger et al 2004). Generally, the absorption intensity at 2900 cm -1 is used as internal standard for determination of the cellulose structural degree in wooden samples (Poletto et al 2014;Odabas et al 2016).…”
Section: Ftir Spectroscopymentioning
confidence: 99%
“…Dried cellulose was cationised according to the procedure described by Odabas and colleagues (Odabas et al, 2016). Briefly, 5 g of cellulose fibres were added to 225 mL THF in a two-necked round-bottom flask equipped with a condenser, and stirred for 1 hour at ambient temperature (21 ± 2 ℃).…”
Section: Cationization Of Cellulose Adsorbentsmentioning
confidence: 99%
“…Because side reactions are promoted by the presence of water (Zaman et al, 2012), THF was used as a solvent. Odabas et al (Odabas et al, 2016) showed that THF plays a "spectator" role, having little if any influence on the cationisation reaction.…”
Section: Characterisationmentioning
confidence: 99%